Mitophagy in atherosclerosis: from mechanism to therapy - Zhang, Yanhong; Weng, Jiajun; Huan, Luyao; Sheng, Song; Xu, Fengqin (Frontiers in Immunology, 2023)
Mitophagy is a kind of autophagy that may selectively eliminate damaged and depolarized mitochondria to maintain mitochondrial activity and cell homeostasis. Several pathways have been found to participate in various steps of mitophagy. Mitophagy plays a significant role in the homeostasis and physiological function of vascular endothelial cells, vascular smooth muscle cells, and macrophages, and is involved in the development of atherosclerosis (AS). At present, many medications and natural chemicals have been proved to alter mitophagy and slow the course of AS. This review serves as an introduction to the mitophagy field for researchers interested in targeting this pathway as part of potential AS management strategy.